OPTIMIZING EUCALYPTUS PELLITA SEEDLING GROWTH THROUGH NPK FERTILIZER AND LIGHT INTENSITY REGULATION - Ratna Puri, Suci; Mahub, Itang Ahmad; Rumondang, Jenny; Handayani, Rajjitha; Hardiyanti, Rizky Ayu; Aulia, Ahmad Khoiril (Jurnal Belantara, 2025)
Eucalyptus pellita is a type of fast-growing plant (fast-growing species). The advantage of this plant is that it is a short rotation or fast-growing plant, with fewer disease attacks. The benefits of the plant are quite numerous and it has high economic value. Considering that the optimal light intensity for eucalyptus seedling growth is not yet known, it is necessary to test the effects of various light intensities using shade in the form of paranet. This research was conducted using a factorial Completely Randomized Design (CRD) with a split-plot experimental pattern consisting of 4 treatment levels. Each treatment was repeated 3 times, The results of the study on the effect of NPK fertilizer and light intensity on the growth of eucalyptus seedlings indicate that the interaction of 5g NPK fertilizer per seedling and 100% light intensity is a better treatment compared to other treatments. This is suspected because eucalyptus is a plant that requires sufficient light intensity to experience the growth of eucalyptus seedlings. The growth of eucalyptus seedlings is influenced by light intensity, which supports the increase in height, stem diameter, and number of leaves. Based on the results of this study, it can be concluded that the treatment with NPK fertilizer and light intensity has a significant effect on increasing stem diameter. In the treatment P2C0, which is NPK fertilizer 7g/seedling and light intensity 100%, there is no significant difference compared to treatments P1C0 and P3C0, which are NPK fertilizers 5g and 9g/seedling at 100% light intensity.